A New Approach to Refine Grains in Al Alloys1. Issue 6 (3rd October 2014) - Bai, Zhihao; Qiu, Feng; Zhang, Tao; Jiang, Qichuan
<x xml:space="preserve">Abstract</x> A new refining grains strategy is reported. A significant refining effect of α‐Al grain from 180 to 32 μm can be achieved by adding 0.2 wt% Zr55Cu30Al10Ni5 metallic glass into Al–Cu melt. This remarkable refinement effect is mainly attributed to the Zr2Cu and ZrCu(B2) crystallization phases, and they will act as the heterogeneous nucleation sites for α‐Al grains because of their high melt points, small, uniform sizes and good lattice mismatch with α‐Al matrix.